Orientasi Kerja Karyawan PT Gans Energi Indonesia Kota Bengkulu - Qingwen, Huang (Universitas Bengkulu, 2025)
The study explored the work orientation of the employees who worked at PT Gans Energi Indonesia in Bengkulu City. In particular, it assessed their perceptions and examined how the perceptions differ based on the classification of employees’ status, which are Chinese and Indonesian as the company operating and managing by Chinese. All employees who had the job contracts were chosen as the sample for the study. The study was conducted using a framework derived from the five dimensions model of work orientation. The work orientation questionnaire with the 25 items was used in the survey. Data were collected using an online survey, and 219 questionnaires were obtained. The results showed that the calling, job, career, social embeddedness and busyness orientations reflected very highly scores on the employees’ perceptions. Individually, Chinese employees tended to be oriented to the calling, job and social embeddedness dimension, and the domestic employees inclined to the career and busyness orientations. Statistically, there was significant differences were found among the work orientations with Chinese respondents tending to hold the calling, job, and social embeddedness orientations, and Indonesian employees inclining to the career and busyness orientations. This study is the first to examine the perception of work orientation. Further, the findings were totally opposite from the demographic data and the condition of workplace. They seem that the concept of the work orientation has to take care carefully. The work culture of each nation and the individual values have to take into account. The discussions, implications and suggestions are discussed.